Pendidikan Karakter dalam Meningkatkan Spiritual Siswa Melalui Pembelajaran Madrasah Diniyah - Saipur Rahman; M. Mahbubi (Student Scientific Creativity Journal, 2024)
Character education is the process of developing students' ability to behave positively, which includes improving various skills that make humans become religious individuals and able to carry out responsibilities as leaders in society. At Madrasah Diniyah Pondok Pesantren Nurul Jadid, character development is carried out through religious learning. This research aims to identify effective learning strategies in improving students' character and spirituality through learning at Madrasah Diniyah at Nurul Jadid Vocational School. This research uses qualitative methods, which focus on natural phenomena or symptoms. In qualitative research, the researcher is directly involved in the process and interactions, capturing meaning from the participant's perspective, not as an outside observer. The learning carried out includes Furudlul Ainiyah material, which aims to equip students with the ability to read and write the Al-Qur'an, understanding of Islamic law (Fiqh), creeds, and obedience in worship. This approach is expected to increase students' spirituality and positive character, as well as prepare them to become individuals capable of carrying out responsibilities in society. Madrasah Diniyah has an important role in forming students' character and spirituality, making them better prepared to face life's challenges with a strong moral and ethical foundation. It is hoped that this research can contribute to the development of effective learning strategies to improve student character and spirituality in religious education environments.